Indoor soundscapes at home during the COVID-19 lockdown in London – Part II: A structural equation model for comfort, content, and well-being. (1st January 2022) - Torresin, Simone; Albatici, Rossano; Aletta, Francesco; Babich, Francesco; Oberman, Tin; Stawinoga, Agnieszka Elzbieta; Kang, Jian
Abstract: The present work constitutes the sequel to the analysis of data from an online survey administered to 464 home workers in London in January 2021 during the COVID-19 lockdown. Perceived affective quality of indoor soundscapes has been assessed in the survey through a previously developed model, as the combination of two perceptual dimensions, one related to comfort (a comfortable – annoying continuum) and the other to content (a full of content – empty continuum). Part I of the study reported on differences in comfort, content, and soundscape appropriateness based on the activity performed at home during the lockdown, i.e. working from home (WFH) and relaxation. Moreover, associations between soundscape dimensions and psychological well-being have been highlighted. Part II of the study deals with the exploration of the influences of several acoustical, building, urban and person-related factors on soundscape dimensions and well-being. A mixed-method approach has been adopted by combining multivariate regression of questionnaire scores with the qualitative analysis of spontaneous descriptions given by respondents. Results showed that several sound sources, urban features, housing characteristics, working modes and demographic factors can influence (positively and negatively) soundscape dimensions differently depending on the task at hand. Notably, the perceived dominance of neighbours' noises during relaxation, moderated by noise sensitivity, and the number of people at home were common factors negatively affecting both comfort and well-being, that partially explained the association between comfortable indoor soundscapes and better mental health. The discussion points out the importance of considering the different impacts that acoustical factors (e.g. sound typology), building (e.g., house size), urban (e.g., availability of a quiet side), situational (e.g., number of people at home), and person-related factors (e.g., noise sensitivity) can provide on building occupants depending on the specific activity people are engaged with at home and the opportunities to foster people's well-being through building, urban and acoustic design.